Differential Effects of Incentive Motivators on Work Performance - Stajković, Alexander D.; Luthans, Fred (Academy of Management Journal, 2001)
In this field experiment, we first compared the performance effects of money systematically administered through the organizational behavior modification (O.B. Mod.) model and routine pay for performance and then compared the effects of O.B. Mod.-administered money, social recognition, and performance feedback. The money intervention based on the O.B. Mod. outperformed routine pay for performance (performance increase = 37% vs. 11%) and also had stronger effects on performance than social recognition (24%) and performance feedback (20%).